2011
DOI: 10.4236/am.2011.212213
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Formation in Tri-Trophic Ratio-Dependent Food Chain Model

Abstract: In this paper, a spatial tri-trophic food chain model with ratio-dependent Michaelis-Menten type functional response under homogeneous Neumann boundary conditions is studied. Conditions for Hopf and Turing bifurcation are derived. Sufficient conditions for the emergence of spatial patterns are obtained. The results of numerical simulations reveal the formation of labyrinth patterns and the coexistence of spotted and stripelike patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It has been shown that such instability should be generic for the two-species predator-prey models 15 (see also 16 ). Complex spatio-temporal ecological dynamics related to the Turing-Hopf 15 17 and Turing-Takens-Bogdanov 15 bifurcations has been discussed. Stationary Turing patterns have been found in realistic models describing plant-parasite 18 , plankton-fish 19 and plant-insect 20 interactions.…”
mentioning
confidence: 99%
“…It has been shown that such instability should be generic for the two-species predator-prey models 15 (see also 16 ). Complex spatio-temporal ecological dynamics related to the Turing-Hopf 15 17 and Turing-Takens-Bogdanov 15 bifurcations has been discussed. Stationary Turing patterns have been found in realistic models describing plant-parasite 18 , plankton-fish 19 and plant-insect 20 interactions.…”
mentioning
confidence: 99%